Prelimenay readiographical study of the blood supply of the ovaries in donkeys - I. Salih, S.; M. Jawad, N.; R. Khalid, F.; A. Khamas, W. (The Iraqi Journal of Veterinary Medicine, 1990)
This preliminary radiographic study was performed with the available instruments to describe the arterial blood supply of the ovaries to establish a base for future studies in this respect due to the importance of the blood supply and its effect on the activities of the ovaries in different phases of estrous cycle. Five she donkeys of different ages were used in this study and in different stages of estrous cycle. The animals were killed and the internal genitalia were carefully dissected to clarify the arterial supply for the injection of the ovarian artery from its origin. (abdominal aorta) in some animals and in the midway between the origin and the ovary in the rest of the animals. Then, CONRAY-480 were injected as a radioopaque contrast media. Radiographs were studied accordingly and the results emphasized the relationship between the activity of the ovaries and their blood supply.